Correlation lengths in quasi-one-dimensional systems via transfer matrices. (17th November 2018) - Hu, Yi; Fu, Lin; Charbonneau, Patrick
ABSTRACT: Using transfer matrices up to next-nearest-neighbour interactions, we examine the structural correlations of quasi-one-dimensional systems of hard disks confined by two parallel lines and hard spheres confined in cylinders. Simulations have shown that the non-monotonic and non-smooth growth of the correlation length in these systems accompanies structural crossovers [Fu et al., Soft Matter13, 3296 (2017)]. Here, we identify the theoretical basis for these behaviours. In particular, we associate kinks in the growth of correlation lengths with eigenvalue crossing and splitting. Understanding the origin of such structural crossovers answers questions raised by earlier studies, and thus bridges the gap between theory and simulations for these reference models. GRAPHICAL ABSTRACT: